The Effects of an 8-Month Multicomponent Training Program in Body Composition, Functional Fitness, and Sleep Quality in Aged People: A Randomized Controlled Trial - Forte, Pedro (2024)
This study examined the effects of an intervention on anthropometrics, body composition, physical fitness, and sleep quality in aged individuals, comparing a control group (N = 11) and an experimental group (N = 13) across two measurement points. Methods: A multicomponent training program of 8 months was adopted as the intervention group. A bioimpedance balance, functional fitness test, and Pittsburgh Sleep Quality Index measured body composition, functional fitness, and sleep quality. Results: Both groups showed minimal changes in body mass and hand grip strength. However, the experimental group experienced significant improvements in physical fitness, including a 26% increase in arm curl repetitions, an 18% reduction in 5 times sit-to-stand (5TSTS) completion time, and a 29% rise in 2-min step test (2MST) steps, indicating enhanced muscle endurance and cardiovascular fitness. Flexibility decreased significantly in the experimental group, while body fat percentage was reduced by 10%. Sleep quality improved by 47% in the experimental group but declined by 14% in the control group. Correlational analysis revealed that better sleep quality was linked to improved fitness performance and reduced body fat in the experimental group, with post-intervention results further confirming the connection between sleep and fat reduction. In the control group, improved sleep quality was associated with higher metabolic rates after 8 months. Conclusions: These findings suggest that the intervention positively impacted physical fitness and sleep quality, with potential benefits for overall health.